Το Υπομνηστικόν του Μιχαήλ Χωνιάτη και οι καστρηνοί - ΠΑΠΑΓΕΩΡΓΙΟΥ, Αγγελική Π. (Byzantina Symmeikta, 2008)
MICHAEL CHONIATES’ ΥΠΟΜΝΗΣΤΙΚΟΝ AND THE TERM KASTRENOI The aim of this paper is to prove that the term kastrenoi, used by Michael Choniates, metropolitan of Athens, in the letter he addressed to the emperor Alexios III Angelos in 1198, denotes the inhabitants within the castle, i.e. the city. There are two different views on the subject, the one expressed by Sp. Lambros in the commentary to his edition of Michael Choniates’ work and the other by Professor Aik. Christophilopoulou. Both believe that the term kastrenos means a member of a military unit. The paper examines Michael Choniates’ passage, as well as other contemporary sources, which prove that the term kastrenos has no military meaning whatsoever, but refers solely to a group of people, usually of the upper class, living inside the walls of a fortified city.